Effect of Interdot Distance on Magnetic Behavior of 2-D Ni Dot Arrays - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
Square array of circular dots with varying interdot spacing in the range of 1-4 mu m has been investigated. The dots were patterned by physical mask. Magnetic properties were explored by the ferromagnetic resonance technique and a micromagnetic simulation based on metropolis algorithm. Evaluation of the resonance fields showed that magnetic anisotropy depends on interdot distance indicating an evidence of interdot coupling in system. The coupling is getting weaker with increasing separation from 1 to 4 mu m. The study revealed that magnetic behavior of the patterned structures can be tuned by changing interdot distance.
Keywords: Circular dot array; ferromagnetic resonance; magnetic anisotropy; magnetic interdot coupling; SPIN-WAVE RESONANCE; FERROMAGNETIC-RESONANCE; SHAPE ANISOTROPY; FILMS; INPLANE; NICKEL; MODES